Problems concerning sharp coefficient functionals of bounded turning functions - Muhammmad Ghaffar Khan; Wali Khan Mashwani; Jong-Suk Ro; Bakhtiar Ahmad (AIMS Mathematics, 2023)
The work presented in this article has been motivated by the recent research going on the Hankel determinant bounds and their related consequences, as well as the techniques used previously by many different authors. We aim to establish a new subfamily of holomorphic functions connected with the hyperbolic tangent function with bounded boundary rotation. We investigate the sharp estimate of the third Hankel determinant for this newly defined family of functions. Moreover, for the defined functions family, the Krushkal inequality, the first four initial sharp bounds of the logarithmic coefficients and the sharp second Hankel determinant of the logarithmic coefficients are given.